LITERATURE EVALUATION OF SHARIA AUDITING IN ZAKAT MANAGEMENT ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW - Yanti, Sri Devi; Abdullah, Muhammad Wahyuddin; Muchlis, Syaiful (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
The purpose of this study is to evaluate the literature related to sharia auditing in OPZ in Indonesia by conducting literature mapping. The research method used is systematic literature review. The literature search used the Google Scholar database with the help of the Publish or Perish 8 application. The article search was carried out using the keyword "Zakat Audit". Based on the systematic literature review conducted on 10 articles spanning 2019-2023, it shows that research in scientific journals related to the topic of sharia auditing in zakat management organizations in Indonesia is dominated by qualitative research methods and it is found that there are three subthemes that are the focus of research related to sharia auditing in zakat management organizations in Indonesia namely, 1) Implementation of sharia audit in zakat management organizations; 2) The role of sharia audit in zakat management organizations, and 3) Problems of sharia audit in zakat management organizations